Microplastics in fish culture ponds: abundance, characterization, and contamination risk assessment - Hossain, M. Belal; Banik, Partho; Nur, As-Ad; Choudhury, Tasrina Rabia; Liba, Samia Islam; Albeshr, Mohammed Fahad; Yu, Jimmy; Arai, Takaomi (Frontiers in Environmental Science, 2023)
Being an emergent contaminant, microplastics (MPs) have gained international focus and have been reported in various ecosystems. Nevertheless, there is currently a lack of information regarding the contamination levels of MPs in aquaculture ponds worldwide. In this study, sediment and water samples were collected from five types of fish ponds, namely, homestead ponds (S1), commercial aquaculture ponds (S2), ponds near a residential area (S3), ponds near a small-scale industrial area (S4), and ponds near a large-scale industrial area (S5) to identify, characterize and assess the contamination risk of MPs. Stereomicroscopic and Fourier-transform infrared spectroscopy (FTIR) analyses revealed that the MPs ranged from 3.33 item/kg to 136.67 item/kg in sediment, and 16.6 item/L to 100 item/L in water samples. Overall, the abundance of MPs was extremely high in S5 followed by S4, S2, S3, and S1 which clearly showed the levels increased with intensity of human activities. The levels of MPs in both sediment and water showed significant differences (p < 0.05) both within and between ponds, as well as in the comparison between water and sediment samples. The concentrations of MPs surpassed those noted in aquaculture ponds of different nations. The majority of MPs consisted of fragments and films in both sediment and water. Furthermore, transparent and white-colored MPs were the prevailing types found in the sediment and water of the aquaculture ponds. Around 34% of MPs present in sediment and 30% in water fell within the size range of 0.5 to 1 mm. Polymers like polypropylene (PP), polyethylene (PE), and polyethylene terephthalate (PET) were prevalent in both sediment and water samples. The contamination factor reached exceptionally elevated levels (> 30 for sediment and > 3 for water), signifying that the sampled regions, particularly S4 and S5 (industrial sites), displayed significant MP contamination. Moreover, the pollution load index values of sediment (3.0 ± 1.5) and water (1.5 ± 0.3) also indicated the areas were contaminated with MPs. Multivariate analysis indicated that the elevated concentration of MPs in the studied region could be attributed to the discharge of effluents and other human-induced activities.